(3LeY YGUes - (3ESeGYjd Hf Ydj Hf MSf GdUYjOj GdbGgQj GdTGaYj, GHf eYdjs ((3ESeGYjd Hf Ydi Hf MSf Hf eYdi s)
(3ChdgG (B:s
(3ShQI GdHbQI hgj gPg GdMQha s
(3BNQgG (B:s
(3Je eG JjSQ ef QhGjI YGUe s
(3Vef eLehY , JQJjHgG (B: 2s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B370s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs